Exploring acute cellular rejection in lung transplantation: insights from donor-derived cell-free DNA analysis - Zajacova, Andrea; Alkhouri, Majd; Guney, Miray; Ferrao, Goncalo; Rezac, David; Vyskocilova, Kristyna; Kotowski, Tereza; Dutkova, Alzbeta; Dvorackova, Eliska; Lischke, Robert; Fila, Libor; Havlin, Jan (Biomedical papers, 2025)
Background. Acute cellular rejection (ACR) is a frequent complication following lung transplantation, yet standardized guidelines for ACR screening remain lacking. This study aimed to compare the current gold standard for ACR evaluation - histological assessment of transbronchial biopsies - with a novel biomarker for allograft monitoring: donor-derived cell-free DNA (dd-cfDNA). Specifically, we investigated whether total cell-free DNA (cfDNA) and both the absolute and percentage values of dd-cfDNA (dd-cfDNA and dd-cfDNA%) could provide valuable insights into detecting ACR and assessing allograft health.Methods. Patients after bilateral lung transplantation between May 2021 and March 2024 were included. Clinically significant ACR cases (ACR+) were defined as samples with histological ACR grade ≥A2 or ACR grade A1 in patients who have received antirejection therapy due to symptoms, CT findings, or lung function decline. Samples with A0 or A1 rejection in clinically stable, untreated patients were classified as controls. Measurements of dd-cfDNA%, dd-cfDNA (cp/mL) and total cfDNA (cp/mL) were obtained at the time of biopsy and compared between cohorts.Results. The median dd-cfDNA concentration was significantly higher in the ACR+ group (61.2 cp/mL, IQR: 38.7-114.1) compared to controls (25.8 cp/mL, IQR: 10.7-65.7; P=0.04). However, no significant differences were observed for dd-cfDNA% and cfDNA.Conclusion. Dd-cfDNA shows promise as a valuable tool for ruling out ACR; however, further research is necessary in order to validate its clinical utility and optimize its implementation. Its negative predictive value supports dd-cfDNA as an effective screening tool for allograft health, nevertheless, further investigation is required.
Keywords: lung transplantation; acute cellular rejection; donor-derived cell-free DNA; biomarkers; non-invasive surveillance